Parkinson's disease and Parkinson's disease medications have distinct signatures of the gut microbiome - Hill‐Burns, Erin M.; Debelius, Justine W.; Morton, James T.; Wissemann, William T.; Lewis, Matthew R.; Wallen, Zachary D.; Peddada, Shyamal D.; Factor, Stewart A.; Molho, Eric; Zabetian, Cyrus P.; Knight, Rob; Payami, Haydeh (Movement disorders, 2017)
ABSTRACT Background There is mounting evidence for a connection between the gut and Parkinson's disease (PD). Dysbiosis of gut microbiota could explain several features of PD. Objective The objective of this study was to determine if PD involves dysbiosis of gut microbiome, disentangle effects of confounders, and identify candidate taxa and functional pathways to guide research. Methods A total of 197 PD cases and 130 controls were studied. Microbial composition was determined by 16S rRNA gene sequencing of DNA extracted from stool. Metadata were collected on 39 potential confounders including medications, diet, gastrointestinal symptoms, and demographics. Statistical analyses were conducted while controlling for potential confounders and correcting for multiple testing. We tested differences in the overall microbial composition, taxa abundance, and functional pathways. Results Independent microbial signatures were detected for PD (P = 4E‐5), participants' region of residence within the United States (P = 3E‐3), age (P = 0.03), sex (P = 1E‐3), and dietary fruits/vegetables (P = 0.01). Among patients, independent signals were detected for catechol‐O‐methyltransferase‐inhibitors (P = 4E‐4), anticholinergics (P = 5E‐3), and possibly carbidopa/levodopa (P = 0.05). We found significantly altered abundances of the Bifidobacteriaceae, Christensenellaceae, [Tissierellaceae], Lachnospiraceae, Lactobacillaceae, Pasteurellaceae, and Verrucomicrobiaceae families. Functional predictions revealed changes in numerous pathways, including the metabolism of plant‐derived compounds and xenobiotics degradation. Conclusion PD is accompanied by dysbiosis of gut microbiome. Results coalesce divergent findings of prior studies, reveal altered abundance of several taxa, nominate functional pathways, and demonstrate independent effects of PD medications on the microbiome. The findings provide new leads and testable hypotheses on the pathophysiology and treatment of PD. © 2017 International Parkinson and Movement Disorder Society